Mendorong Green Entrepreneurial Intention Melalui Green Economy dan Green Entrepreneurial Orientation - Kartika Nuringsih; Nuryasman MN; Jovita Aurellia Rosa (Fakultas Ekonom dan Bisnis, Universitas Tarumanagara, 2022)
Aligning with the achievement of the sustainable development goals (SDGs) agenda in 2030 and the G-20 presidency in Indonesia, a study was conducted on entrepreneurship learning in higher education. The purpose of this research is to explore the relationship between green economy, green entrepreneurial orientation and green entrepreneurial intention among university students. Educational institutions as stakeholders are responsible for organizing entrepreneurship learning that is in line with global community commitments in dealing with climate change and achieving sustainable prosperity. The study involved 175 business school students in Jakarta using convenience sampling. The results show the direct effect of green economy and green entrepreneurial orientation on green entrepreneurial intention and the formation of a mediating effect through green entrepreneurial orientation. The significance of the three variables forms the green triangle model so that it can be considered as a basis for learning mechanisms for eco-friendly entrepreneurship. Efforts to foster student interest are formed through green entrepreneurial orientation so that this construct is important in building environmentally-oriented entrepreneurship. Stakeholder collaboration is needed in implementing green entrepreneurship as pathway in an achieving SDGs agenda and dealing with climate change.